Two new species of encrusting sponge (Porifera, family Crellidae) from eastern Canada - Goodwin, C.; Dinn, C.; Nefedova, E.; Nijhof, F.; Murillo, F.J.; Nozères, C. (Canadian Journal of Zoology, 2021)
Two new species of Crellidae Dendy, 1922 from the east coast of Canada are described. The first is Crella (Pytheas) cutis sp. nov., a massively encrusting species of Crella (Pytheas) collected from depths of 84 to 249 m in the Gulf of St. Lawrence and on the Scotian Shelf. The second is Crellomima mehqisinpekonuta sp. nov., a thinly encrusting sponge found at diving depths in the Bay of Fundy. We also report the first records of Crellomima derma Hentschel, 1929 from outside the type locality (Barents Sea). All known species of Crellomima are reviewed based on type material.